Spacing Out: Web 3D and the Reconstruction of Archaeological Sites - Milbank, Thomas L. (Tufts Archival Research Center, 2005)
The emergence of high-speed processors with 3D graphics acceleration and the accessibility of high-speed internet connections have propelled web 3D from a frustrating to a viable internet technology. Without a doubt, the addition of spatial dimension to customary 2D web graphics can be visually gripping. But greater potential for the technology lies beyond its ability to command attention. Web 3D presents students and scholars alike with a new tool for visualizing and understanding ancient sites. Fundamentally, 3D digital reconstruction allows architecture, sculpture, and other remains to be considered in their respective contexts as a whole, rather than as individual items divorced from their intended settings. At the same time, digital reconstruction can incorporate a distinction between the "real" and the "hypothetical" just as found in other types of modern restoration work. The Perseus Project is currently preparing 3D models of various archaeological sites. These will be linked to other related materials already in its digital library: maps; plans; photographs; QTVR walkthroughs; site, architecture, and object catalogs; and literary and historical documents. In part, the models are intended as databases of geographic and architectural information in their own right. They are also intended to serve as the underpinning for a contextual presentation of architectural and freestanding sculptures. This paper surveys Perseus' work on the Apollo sanctuary at Delphi. It addresses both the process of digital modeling and the method used to integrate the model with Perseus' existing tools and databases.